Involvement of Nail Apparatus in Pemphigus Vulgaris in Ethnic Poles Is Infrequent - Pietkiewicz, Pawel; Bowszyc-Dmochowska, Monika; Gornowicz-Porowska, Justyna; Dmochowski, Marian (Frontiers in Medicine, 2018)
Pemphigus vulgaris lesions have a tendency to localize around natural body orifices. The aim here was to analyze the involvement of nail apparatus in pemphigus vulgaris. Sixty seven ethnic Poles suffering from pemphigus vulgaris on photographic files archiving initial presentation were retrospectively evaluated. Pemphigus vulgaris was diagnosed using combination of clinical data, H+E histology, direct immunofluorescence of plucked scalp hair and/or perilesional tissue also for IgG1 and IgG4 deposits evaluation, indirect immunofluorescence on mosaic substrate and/or monkey esophagus, mono-analyte ELISA with desmoglein 1/3 or multi-analyte ELISA. The nail apparatus involvement was found in 9 of 67 patients (13.4%; 3 females and 6 males). Periungual fingernail lesions were found in 6 patients (2 females, 4 males), whereas periungual toenail lesions in just 3 patients (1 female, 2 males). Our patients nail apparatus changes included, by order of frequency, paronychia, nail discoloration, onychorrhexis, Beau lines, periungual hemorrhages, onychomadesis, cross-ridging, onycholysis and trachyonychia. The average time between the onset, as recalled by patients, and the diagnosis of pemphigus vulgaris with direct immunofluorescence was not statistically different in PV patients with and without nail apparatus lesions. In this article the molecular and immunological rationale for of periungual involvement is discussed. Our single-center study suggests that nail apparatus involvement is infrequent in pemphigus vulgaris in ethnic Poles. Due to the fact that nail apparatus lesions in pemphigus vulgaris may clinically resemble onychomycosis, giving the proper diagnosis can be difficult particularly when other lesions are overlooked or misinterpreted.